(untitled)
The concept of δ-β_I -paracompactness in ideal topological spaces is introduced as a weaker form of β-paracompactness, which was looked at in YO. This study examines several characterizations of δ-β_I -paracompact spaces and its subsets. Furthermore, we investigate the invariants of δ-β_I -paracompactness through functions. , number=1, journal=European Journal of Pure and Applied Mathematics, year=2025, month=Jan., pages=5570